Pituitary Adenoma and Hyperprolactinemia Accompanied by Idiopathic Granulomatous Mastitis - Sebahattin Destek; Vahit Onur Gul; Serkan Ahioglu; Kursat Rahmi Serin (Case Reports in Endocrinology)
Idiopathic granulomatous mastitis (IGM) is a rare chronic inflammatory disease of the breast, and its etiology remains not fully elucidated. IGM is observed more often in patients with autoimmune disease. Hyperprolactinemia is observed during pregnancy, lactation, and a history of oral contraceptive use. A 39-year-old patient with no history of oral contraceptive use presented with complaints such as redness, pain, and swelling in her left breast. Ultrasound and magnetic resonance imaging (MRI) revealed a suspicious inflamed mass lesion. Core biopsy was performed to exclude breast cancer and to further diagnose. The breast abscess was drained and steroids were given for treatment. In order to monitor any progression during the three months of treatment, hormone levels were routinely examined. Prolactin level was above the reference range, and pituitary MRI revealed a pituitary prolactinoma. After treatment with prolactin inhibitors, IGM also improved with hyperprolactinemia. This report emphasizes attention to hyperprolactinemia in cases of IGM diagnosis and treatment.